Object of Misappropriation in an Authorship Crime and its Meaning for Qualification - Steponavičiūtė, Ramunė (Teisė, 2020)
This article analyses one element of corpus delicti of misappropriation of authorship, criminalised in Lithuanian Criminal Code Article 191 – the object (or the protected good) of a crime. The quality of Lithuanian national regulation and the scope of object of misappropriation of authorship, which affects the qualification of the crime, is evaluated by comparing it with other European Union countries’ criminal legal regulation of intellectual property.